Characterization and cost-benefit analysis of 3D-printed acrylonitrile butadiene styrene (ABS) dry conductive electrodes as reusable electrodes for surface electromyography (EMG) applications - Licayan, Joshua H. (Animo Repository, 2022)
This study investigated the use of 3D-printed dry electrodes for surface electromyography (sEMG). Solid freeform fabrication (SFF) and fused deposition modeling (FDM) is a promising fabrication method that has potential applications in EMG, especially in developing wearable EMG. A 3D printer was used to fabricate conductive acrylonitrile butadiene styrene (ABS) electrodes in different layer heights. The 3D printed electrodes’ Young’s and Shear Moduli and tensile and shear yield, ultimate, and fracture points were determined using a Materials Testing System. The arithmetic average roughness height, Ra, and the root mean square roughness, Rq, of the printed electrodes’ surfaces were quantified through macro imaging and image processing and analysis software. The resistances of the electrodes were also measured using a digital multimeter. A comparative analysis between the signal-to-noise ratio (SNR) of the printed conductive ABS electrodes and the commercial standard Ag/AgCl electrodes. A cost-benefit analysis was also undertaken to determine the cost-effectiveness of the 3D-printed conductive ABS electrodes compared to the commercial standard Ag/AgCl electrodes. The 3D-printed conductive ABS electrodes were then attached to the volunteer’s biceps brachii muscle and corresponding EMG data was eventually fetched using the MyoWare muscle sensor module. Statistical analysis has shown that there was no significant differences between the SNRs of the 3D-printed conductive ABS electrodes and the commercial standard Ag/AgCl electrodes when used for EMG on biceps as Myoware Muscle sensors. Although 3D-printed conductive ABS electrodes has shown the highest SNR with layer height of 0.20 mm. With tensile strength of 1.53 ± 0.01 Gpa and shear stress of 0.15 ± 0.01 Gpa empirically derived for ABS filament material using PASCO ME-8244 Tensile-Sress Test, optimal SNR performance was observed for 3d-printed conductive ABS electrodes with a layer height of 0.20 mm and surface roughness of 26.01 nm. Furthermore, the cost-benefit analysis has shown that the cost-effectiveness of the printed electrodes, specifically with layer heights of 0.16mm and 0.20mm, was comparable to that of the Ag/AgCl electrode with Php 0.02/use difference. Thus, 3D-printed ABS dry conductive electrodes can be an alternative electrode besides commercial standard Ag/AgCl electrodes with no significant technical difference in terms of its SNR values and with comparable cost-effectiveness in terms of price per use value.